2018
DOI: 10.1093/tas/txy090
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of dietary electrolyte balance on nursery pig performance1

Abstract: Increasing dietary electrolyte balance (dEB) has been reported to linearly improve pig growth performance up to approximately 200 to 250 mEq/kg. However, recent data indicate that increasing dietary dEB reduced growth performance of nursery pigs. To attempt to solve this discrepancy, a total of 2,880 weanling pigs (327 × 1,050; PIC, Hendersonville, TN; 5.2 kg initial BW) were used to determine the effects of increasing dEB on nursery pig performance. Pens of pigs were blocked by BW and gender on arrival. Withi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 12 publications
1
5
0
Order By: Relevance
“…NRC (2012) reported that the optimal dEB for pigs is approximately 250 mEq/kg. Jones et al (2019) observed that reduced levels of nursery dietary dEB in phase one (84, 137, 190, and 243 mEq/kg) and phase 2 (29, 86, 143, and 199 mEq/kg) resulted in poorer growth of weanling piglets. In this study, the insignificant growth differences may have resulted from the number of test days.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…NRC (2012) reported that the optimal dEB for pigs is approximately 250 mEq/kg. Jones et al (2019) observed that reduced levels of nursery dietary dEB in phase one (84, 137, 190, and 243 mEq/kg) and phase 2 (29, 86, 143, and 199 mEq/kg) resulted in poorer growth of weanling piglets. In this study, the insignificant growth differences may have resulted from the number of test days.…”
Section: Discussionmentioning
confidence: 99%
“…At weaning, young pigs are exposed to psychosocial and physical stressors accompanied by marked changes in gastrointestinal physiology, microbiology and immunology, which may result in poor growth performance and increased mortality (Hampson, 1986; Heo et al, 2012; Hu et al, 2013; Pluske et al, 1997). Dietary ion content is known to alter the acid–base balance, osmotic pressure and nutrient metabolism in animals (Dersjantli et al, 2002; Guzmán‐Pino et al, 2015; Seifter & Chang, 2017), which can influence growth performance (Jones et al, 2019). Calcium (from limestone), phosphorus (from calcium phosphate), and sodium and chloride (from salt and sodium bicarbonate) are often added to the diet to satisfy animal growth requirements (NRC, 2012).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…(2017) concluded that weaned pigs achieved the optimal growth rate when fed diets containing 166 to 250 mEq/kg dEB. Jones et al. (2019) observed that in stages 1 and 2, the optimal dEB for weaned piglets was 243 and 199 mEq/kg, respectively.…”
Section: Introductionmentioning
confidence: 92%